Processing method for adjusting yield of ethylene and propylene in catalytic cracking process of n-butane

By using the integration method of the twin-bed layer and the coupling of the dehydrogenation performance catalyst and the cracking performance catalyst in the catalytic cracking process of n-butane, the problem of low yields of ethylene and propylene in the prior art is solved, and efficient catalytic performance is achieved and Product distribution regulation significantly improves the yield of low-carbon olefins.

CN119191931APending Publication Date: 2024-12-27BEIJING INST OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527651.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, the yields of ethylene and propylene are low during the catalytic cracking of n-butane, and the uneven microporous structure and surface acidity distribution of the catalyst lead to an increase in side reactions, reducing the yield of low-carbon olefins.

Method used

The integration method of twin beds is adopted, and the dehydrogenation performance catalyst is coupled with the cracking performance catalyst to form a composite catalyst. The product distribution is regulated in the reactor through pretreatment and optimization of reaction conditions to improve the yield of ethylene and propylene.

Benefits of technology

By optimizing the coupling method of the catalyst, the catalytic performance is improved, the yield of ethylene and propylene and the conversion of n-butane are significantly improved, the product distribution is regulated, and the product value is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191931A_ABST
    Figure CN119191931A_ABST
Patent Text Reader

Abstract

The invention relates to a processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane, which comprises the following steps: S1, providing a dehydrogenation performance catalyst and a cracking performance catalyst, coupling the two catalysts to obtain a composite catalyst, mixing the composite catalyst and quartz sand, and filling the mixture into a reactor for pretreatment; and S2, providing a mixed feed gas flow of n-butane and N2, and under reaction conditions, contacting the mixed feed gas flow with the composite catalyst in the reactor to carry out catalytic cracking reaction. According to the invention, by optimizing a coupling mode between different catalytic activities of the catalysts, an integration mode of optimally combining an upper-layer dehydrogenation performance catalyst and a lower-layer cracking performance catalyst is constructed, so that the catalytic performance of cascade reaction is improved, and n-butane is firstly subjected to dehydrogenation reaction on the dehydrogenation performance catalyst to generate butene; butene is further diffused to the surface of the cracking performance catalyst to generate cracking performance, so that the cooperation of active sites and acidic sites is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical industry, and in particular to a processing method for adjusting the yields of ethylene and propylene in the process of catalytic cracking of normal butane. Background Art

[0002] Low-carbon olefins such as ethylene and propylene are the basic raw materials for the production of organic chemical products. Their market demand is constantly increasing, and increasing the output of low-carbon olefins has become an issue that urgently needs to be addressed. At present, about 70% of low-carbon olefins come from steam cracking processes, but there are many shortcomings, such as high reaction temperature, high energy consumption, and fixed product distribution. They can no longer meet the world's current requirements for the sustainable development of the petrochemical industry with "low carbon, green, and high efficiency". "Refining and chemical integration" promotes the transformation and upgrading of petrochemicals. Compared with traditional naphtha steam cracking technology, light hydrocarbons and naphtha catalytic cracking technology can achieve directional high-yield light olefins and by-product aromatics on the basis of reducing energy consumption, hydrogen consumption, and avoiding a large number of intermediate processes, while significantly reducing comprehensive energy consumption and carbon emissions.

[0003] Catalytic cracking reaction is a typical parallel-sequential reaction. The target products such as ethylene and propylene are more active than the raw material alkanes, and are prone to secondary reactions, resulting in a decrease in the yield of low-carbon olefins. Therefore, how to achieve high-selectivity catalytic cracking reaction process regulation while ensuring full conversion of the raw materials and maximizing the inhibition of secondary reactions is the key. At present, HZSM-5 molecular sieve catalysts are widely used in catalytic cracking reactions due to their good hydrothermal stability, adjustable silicon-aluminum ratio and unique pore structure. However, its microporous structure characteristics limit the efficient diffusion of reactant and product molecules, and its surface acidity is unevenly distributed, so that small molecule products continue to undergo side reactions such as aromatization and hydrogen transfer at acidic sites, resulting in a decrease in the yield of low-carbon olefins.

[0004] Patent CN202010022024.2 provides a catalyst for producing light olefins by catalytic cracking of hydrocarbons and a preparation method thereof. The catalyst has good catalytic cracking activity of hydrocarbons and selectivity for ethylene and propylene. Patent CN202210420888.9 provides a catalytic composition for producing olefins from light alkanes and a preparation method thereof. The catalytic composition is placed in a reactor to simultaneously complete the dehydrogenation catalytic process and the catalytic cracking process, saving the investment cost of the equipment and effectively improving the conversion rate of light alkanes and the selectivity of light olefins. The above patents can effectively enhance the conversion rate of alkanes and the yield of light olefins, but the yield of light olefins still needs to be further improved. Summary of the invention

[0005] The purpose of the present invention is to provide a processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, solve the problem of low yield of preparing light olefins by catalytic cracking of alkanes in the prior art through the integration of double beds, and effectively regulate the product distribution.

[0006] To achieve the above object, the present invention provides a processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, which comprises the following steps:

[0007] Step S1. providing a dehydrogenation catalyst and a cracking catalyst, coupling the dehydrogenation catalyst and the cracking catalyst to obtain a composite catalyst, and then mixing the composite catalyst and quartz sand and loading them into a reactor for pretreatment;

[0008] Step S2. providing a mixed feed gas flow of n-butane and N2, and contacting the mixed feed gas flow with a composite catalyst in a reactor under reaction conditions to carry out a catalytic cracking reaction.

[0009] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, the dehydrogenation catalyst in step S1 is selected from CoO x @S-1, one of Pt / Al2O3, ZrO2, Ga2O3 / ZrO2, the cracking performance catalyst is a molecular sieve catalyst, and the molecular sieve catalyst is selected from one of ZSM-5 and SAPO-34.

[0010] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane, the coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically comprises the following steps: mixing the dehydrogenation catalyst and the cracking catalyst powder, then extruding and molding, and sieving to 40-60 mesh to obtain a composite catalyst.

[0011] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane, the coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically comprises the following steps: the dehydrogenation catalyst and the cracking catalyst are extruded and sieved to 40-60 mesh respectively, and mixed to obtain a composite catalyst.

[0012] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane, the coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically comprises the following steps: the dehydrogenation catalyst and the cracking catalyst are extruded and sieved to 40-60 mesh respectively, and then filled in a double bed manner, the dehydrogenation catalyst is filled in the upper layer of the double bed, and the cracking catalyst is filled in the lower layer of the double bed to obtain a composite catalyst.

[0013] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane, the coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically comprises the following steps: the dehydrogenation catalyst and the cracking catalyst are extruded and sieved to 40-60 mesh respectively, and then filled in a double bed manner, the cracking catalyst is filled in the upper layer of the double bed, and the dehydrogenation catalyst is filled in the lower layer of the double bed to obtain a composite catalyst.

[0014] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, the mass ratio of the dehydrogenation catalyst to the cracking catalyst in the composite catalyst in step S1 is 1 to 3.

[0015] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane, the pretreatment in step S1 is specifically as follows: 0.1-0.2g of the composite catalyst is evenly mixed with 1-2g of quartz sand and then loaded into the constant temperature zone in the reactor, followed by heating to 550°C-600°C under a 30-60ml / min N2 atmosphere, keeping the temperature unchanged, oxidizing for 30min under a 30-60ml / min air atmosphere, then purging for 5-10min under a 30-60ml / min N2 atmosphere, and then reducing for 30min under a 30-60ml / min H2 and Ar mixed gas atmosphere.

[0016] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, in step S2, C4H 10 The volume ratio of N2 is 1-4:6-9, and the reaction conditions include: the flow rate of the mixed feed gas flow is 20-50 mL / min, the reaction time is 3.5-5 h, and the reaction temperature is 550° C.-600° C.

[0017] Preferably, in the processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, the composite catalyst is used as a catalyst for the catalytic cracking reaction of n-butane.

[0018] Beneficial effects:

[0019] The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane of the present invention optimizes the coupling mode between the different catalytic activities of the catalysts, constructs the integration mode of the optimal combination of the upper dehydrogenation performance catalyst and the lower cracking performance catalyst, improves the catalytic performance of the series reaction, n-butane first undergoes a dehydrogenation reaction on the dehydrogenation performance catalyst to generate butene, and the butene further diffuses to the surface of the cracking performance catalyst to generate cracking performance, thereby achieving the coordination of active sites and acid sites, and further regulating the product distribution, which has high industrial value and economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a graph of n-butane conversion rates of different combinations in Examples 1-2 of the present invention and Comparative Examples 1-2.

[0021] Figure 2 This is a graph showing the ethylene + propylene yields of different combinations in Example 1-2 of the present invention and Comparative Example 1-2.

[0022] Figure 3 This is a graph showing the n-butane conversion rates of different mass ratios of the best combination in Example 1-2 of the present invention and Comparative Example 1-2.

[0023] Figure 4 This is a graph showing the yields of ethylene + propylene at different mass ratios of the best combination of Example 1-2 of the present invention and Comparative Example 1-2. DETAILED DESCRIPTION

[0024] The present invention is described below by means of the best embodiments. It should be known to those skilled in the art that the embodiments are only used to illustrate the present invention rather than to limit the scope of the present invention.

[0025] Example 1

[0026] Preparation of 1% CoO x @S-1 catalyst, the preparation method comprises the following steps:

[0027] Step S1: Preparation of 1% CoO by evaporation impregnation method x / SiO2 as a silicon source, specifically: 4g SiO2 was dissolved in 40mL anhydrous ethanol, stirred for 30min, and ultrasonicated for 30min until completely dissolved to obtain a SiO2 solution; 0.19754g cobalt nitrate was dissolved in 4mL anhydrous ethanol, stirred for 30min, and ultrasonicated for 30min until completely dissolved to obtain a cobalt nitrate solution, the dissolved SiO2 solution was placed in a 90°C oil bath, and the cobalt nitrate solution was added dropwise, evaporated until the ethanol was completely volatilized to obtain a mixed slurry, the mixed slurry was dried in an oven at 100°C for 3h, and after drying, it was calcined in a muffle furnace at 350°C for 3h to prepare 1% CoO x / SiO2 silicon source;

[0028] Step S2: Prepare Na-type ZSM-5 by hydrothermal method with tetrapropylammonium hydroxide / sodium hydroxide / silicon source / water, specifically: add 8.94 g water to 4.92 g tetrapropylammonium hydroxide solution, stir at room temperature for 30 min, then add 0.12 g sodium hydroxide solution, stir for 30 min, add 3.5 g 1% CoO x / SiO2 silicon source was stirred for 12 hours to obtain a mixed solution, and finally the mixed solution was transferred to a reactor for crystallization at 180°C for 24 hours. After the crystallization, the mixed solution was centrifuged until the aqueous solution was clear and transparent. The slurry after centrifugation was placed in an oven at 80°C for drying for 5 hours. After drying, it was taken out and placed in a muffle furnace, and calcined at 550°C for 6 hours to obtain Na-type ZSM-5 molecular sieve;

[0029] Step S3: Ion exchange to prepare 1% CoO x @S-1 catalyst, specifically: ion exchange was carried out in a 90℃ oil bath with stirring, each time for 2h, for a total of 3 times, each ion exchange included: using 1mol / L ammonium chloride solution to carry out ammonium exchange on Na-type ZSM-5 molecular sieve, 1g catalyst requires 10mL ammonium chloride solution, ion exchange once, centrifugal drying once, centrifugation until the aqueous solution is clear and transparent, the slurry after centrifugation was dried in an oven at 80℃ for 2h, and finally after drying, it was taken out and placed in a muffle furnace, calcined at 550℃ for 6h, and the ion exchange was repeated 3 times to obtain 1% CoO x @S-1 catalyst.

[0030] Example 2

[0031] The HZSM-5 catalyst is prepared, and the preparation method comprises the following steps:

[0032] Step S1: 8.94 g of water was added to 4.92 g of TPAOH, and the mixture was stirred at room temperature for 30 min. Then, 0.12 g of NaOH was added, and the mixture was stirred for 30 min. Then, 0.06 g of sodium aluminate was added, and the mixture was stirred for 1 h. Then, 4 g of SiO2 was added, and the mixture was stirred for 12 h to obtain a mixed solution. Finally, the mixed solution was transferred into a reactor and crystallized at 180° C. for 24 h, and centrifuged and dried at 80° C. for 3 h.

[0033] Step S2: performing ion exchange in a 90°C oil bath with stirring, each time for 2 hours, for a total of 3 times, each ion exchange comprising: using 1 mol / L ammonium chloride solution to perform ammonium exchange on the Na-type ZSM-5 molecular sieve, 10 mL of ammonium chloride solution is required for 1 g of the catalyst, the ion exchange is performed once, and then centrifuged until the aqueous solution is clear and transparent, and then dried in an oven at 80°C for 2 hours. Finally, after drying, the catalyst is taken out and placed in a muffle furnace, calcined at 550°C for 3 hours, and the ion exchange is repeated 3 times to prepare a HZSM-5 catalyst.

[0034] Comparative Example 1

[0035] A 1% Co-HZSM-5 catalyst is prepared, the preparation method comprising the following steps:

[0036] Step S1: 4 g SiO2 (m1) was placed in an eggplant-shaped flask, and deionized water was added dropwise thereto, with continuous shaking. When the carrier reached the critical state of adsorption saturation, the addition was stopped, and the mass of SiO2 at this time (m2 (g)) was weighed. The water absorption rate c of the carrier is calculated, and the water absorption rate of SiO2 is obtained by taking the average value of three measurements; and the SiO2 is pretreated, and the SiO2 pretreatment is dried in a blast oven at 100°C for 12 hours;

[0037] Step S2: Calculate the volume of the impregnation solution required for equal volume impregnation according to the water absorption rate of SiO2 measured in step S1 (4g SiO2 requires 4.8g deionized water), and then prepare a 1% cobalt nitrate solution that meets the requirements according to the result;

[0038] Step S3: 0.1983 g of cobalt nitrate was dissolved in 4.8 g of deionized water and uniformly added dropwise onto 4 g of SiO2 pretreated in step S1, with continuous shaking at a rate of 60 rpm for 20 min to mix evenly, and allowed to stand for 24 h, and placed in a 100° C. oven to dry for 5 h. After drying, the mixture was taken out and placed in a muffle furnace, and calcined at 350° C. for 3 h.

[0039] Step S4: 8.94 g of water was added to 4.92 g of tetrapropylammonium hydroxide solution, stirred at room temperature for 30 min, then 0.12 g of sodium hydroxide solution was added, stirring continued for 30 min, then 0.06 g of sodium aluminate was added, stirred for 1 h, and the silicon source CoO was added. x / SiO2 was stirred for 12 hours, and finally transferred into a reactor for crystallization at 180℃ for 24 hours. After the crystallization, the aqueous solution was centrifuged until it was clear and transparent, and then dried in an oven at 80℃ for 5 hours. After drying, it was taken out and placed in a muffle furnace, and calcined at 550℃ for 6 hours to obtain Na-type HZSM-5 molecular sieve;

[0040] Step S5: Carry out ion exchange in a 90°C oil bath with stirring, each time for 2 hours, for a total of 3 times. Specifically, the ion exchange is as follows: use a 1 mol / l ammonium chloride solution to carry out ammonium exchange on the Na-type ZSM-5 molecular sieve, 10 ml of ammonium chloride solution is required for 1 g of the catalyst, and the ion exchange is performed once. After that, the aqueous solution is centrifuged until it becomes clear and transparent, and then dried in an oven at 80°C for 2 hours. Finally, after drying, the solution is taken out and placed in a muffle furnace, and calcined at 550°C for 3 hours. The ion exchange is repeated 3 times to obtain a Co-HZSM-5 catalyst.

[0041] Comparative Example 2 Prepare a loaded Co / HZSM-5 catalyst, specifically comprising the following steps: Take the HZSM-5 molecular sieve prepared in Example 2 and place it in an eggplant-shaped flask, calculate the volume of cobalt nitrate solution required for the equal volume impregnation method according to the experimentally determined water absorption rate of the HZSM-5 molecular sieve of 0.7%, and prepare a cobalt nitrate solution that meets the requirements according to the result, and uniformly drop a cobalt nitrate solution having a mass concentration of 1.25% (calculated according to the best highly dispersed Co-HZSM-5 (1wt%) ICP (actual Co mass fraction is 1.25%)) and a volume of 0.56mL on the HZSM-5 molecular sieve catalyst, and oscillate continuously during the period, at a rate of 60 rpm and an oscillation time of 20min to mix evenly, let it stand for 24h, dry for 5h, and then place it in a muffle furnace and calcine at 550°C for 3h to obtain a Co / HZSM-5 catalyst.

[0042] The method for determining the water absorption rate of HZSM-5 molecular sieve is as follows: weigh three groups of 1.5g HZSM-5 respectively, dry them in a 120℃ forced air oven for 6h to obtain pretreated HZSM-5 for use; weigh three groups of 1g pretreated HZSM-5 respectively and place them in eggplant-shaped flasks. The eggplant-shaped flasks used have different masses. At this time, weigh the total mass of the eggplant-shaped flask and HZSM-5 to be 80.5g, 80.2g, and 49.008g, and then add deionized water dropwise, shaking the eggplant-shaped flask by hand during the period at a shaking rate of 60 rpm; the oscillation time is 20min, and the dropwise addition is stopped when HZSM-5 reaches the critical state of adsorption saturation. At this time, weigh the total mass of the eggplant-shaped flask, HZSM-5 and deionized water to be 81.2g, 80.7g, and 49.308g, according to The water absorption rate of the carrier was 0.7% as the average value of three measurements.

[0043] The performance test of the catalyst prepared by integrating the active components of the catalysts of Example 1-2 and Comparative Example 1-2 was applied to the catalytic cracking reaction of n-butane:

[0044] Composite catalyst 1: 0.1 g 1% CoO x @S-1 was mixed with 0.1g HZSM-5 catalyst powder, then extruded and sieved to 40-60 mesh, named Powder-mixing-HZSM-5 / 1%CoO x @S-1, evenly mixed with 0.2g 40-60 mesh quartz sand;

[0045] Composite catalyst 2: 0.1 g 1% CoO x @S-1 and 0.1g HZSM-5 catalyst were extruded and sieved to 40-60 mesh, and then the two were evenly mixed with 0.2g 40-60 mesh quartz sand, named Granule-mixing-HZSM-5 / 1%CoOx @S-1;

[0046] Composite catalyst 3: 0.1 g 1% CoO x @S-1 and 0.1g HZSM-5 catalyst were extruded and sieved to 40-60 mesh, and then mixed with 0.1g 40-60 mesh quartz sand and filled in double beds. 1% CoO x @S-1 is on the upper layer, HZSM-5 is on the lower layer, named as 1%CoO x @S-1 / HZSM-5;

[0047] Composite catalyst 4: 0.1 g 1% CoO x @S-1 and 0.1g HZSM-5 catalyst were extruded and sieved to 40-60 mesh, and then mixed with 0.1g 40-60 mesh quartz sand and filled in double layers, with HZSM-5 on the upper layer and 1% CoO x @S-1 is in the lower layer, named HZSM-5 / 1%CoO x @S-1;

[0048] A processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, wherein the method comprises the following steps:

[0049] Step S1. 0.2 g of composite catalyst 1, composite catalyst 2, composite catalyst 3 and composite catalyst 4 were respectively mixed evenly with 2 g of quartz sand and loaded into the constant temperature zone in the reactor, and then heated to 550° C. under 30 ml / min N2 atmosphere, maintained at 550° C., oxidized for 30 min under 30 ml / min air atmosphere, and then purged for 5 min under 30 ml / min N2 atmosphere, and then reduced for 30 min under 30 ml / min H2 and Ar mixed gas atmosphere, with the volume ratio of H2 to Ar being 5:95;

[0050] Step S2. Provide a mixed feed gas stream of n-butane and N2, and introduce 40 ml / min 10% C4H 10 / N2 is reacted, and the mixed feed gas flow is contacted with composite catalyst 1, composite catalyst 2, composite catalyst 3 and composite catalyst 4 in the reactor respectively to carry out catalytic cracking reaction. The reaction temperature is 550°C and the reaction time is 3.5h.

[0051] The performance test of the catalysts of Comparative Examples 1 and 2 was performed when they were applied to the catalytic cracking reaction of n-butane, which specifically included the following steps: 0.2 g 40-60 mesh 1% Co-HZSM-5 and 0.2 g 1% Co / HZSM-5 catalysts were uniformly mixed with 2 g 40-60 mesh quartz sand respectively, and then placed in a constant temperature zone of a stainless steel fixed bed reactor with an inner diameter of 8 mm for pretreatment, wherein the pretreatment was specifically: programmed heating to 550° C. under a 30 ml / min N2 atmosphere, and oxidized at 550° C. under a 30 ml / min air atmosphere for 30 min, then purged under a 30 ml / min N2 atmosphere for 5 min, and then reduced under a 30 ml / min 5% H2 / Ar mixed gas atmosphere for 30 min; a mixed feed gas flow of n-butane and N2 was provided, and 40 ml / min 10% C4H 10 / N2 was reacted, and the mixed feed gas flow was contacted with 1% Co-HZSM-5 catalyst and Co / HZSM-5 catalyst in the reactor respectively to carry out catalytic cracking reaction. The reaction temperature was 550°C and the reaction time was 3.5h.

[0052] like Figure 1-4 As shown, Figure 1 It is a graph of n-butane conversion rate of different combinations in Example 1-2 and Comparative Example 1-2; Figure 2 Graph showing the yields of ethylene + propylene in different combinations in Example 1-2 and Comparative Example 1-2;

[0053] Figure 3 It is a graph of n-butane conversion rates of different mass ratios of the best combination in Example 1-2 and Comparative Example 1-2;

[0054] Figure 4 This is a graph showing the ethylene + propylene yields at different mass ratios of the best combination of Example 1-2 and Comparative Example 1-2.

[0055] (1) Calculation of reaction process parameters

[0056] The conversion rate is calculated from the mass of n-butane before and after the reaction, and the selectivity is calculated by calculating the corresponding mass of each component. The specific method is as follows:

[0057] The conversion rate is calculated as shown in formula (1.1):

[0058]

[0059] The product selectivity is calculated as shown in formula (1.2):

[0060]

[0061] Where m i is the mass corresponding to the product with carbon number i, and i is the number of carbon atoms in the product.

[0062] When comparing the same bed height, HZSM-5, 1% CoO x @S-1、Powder-mixing-HZSM-5 / 1%CoO x @S-1、Granule-mixing-HZSM-5 / 1%CoO x @S-1, 1% CoO x @S-1 / HZSM-5, HZSM-5 / 1%CoO x @The influence of different bed forms of S-1, 1% Co-HZSM-5 and 1% Co / HZSM-5 on catalytic performance.

[0063] from Figure 1-2 It can be seen that the butane conversion rate of HZSM-5 single bed component is 8.17%, and the ethylene + propylene yield is 4.68%; 1% CoO x @S-1 single bed component butane conversion rate is 37.4%, ethylene + propylene yield is 1.23%, after the introduction of dehydrogenation component can significantly increase ethylene + propylene yield and butane conversion rate, and by adjusting the active component combination, ethylene + propylene yield changes significantly; when the active sites are closest, 1% Co-HZSM-5 has a n-butane conversion rate of 24.1%, ethylene + propylene yield is 5.55%, and the catalytic activity is significantly better than that of 1% Co / HZSM-5 prepared by traditional impregnation method; by further expanding the distance between active sites, Powder-mixing-HZSM-5 / 1% CoO x @S-1、Granule-mixing-HZSM-5 / 1%CoO x @S-1 catalyst combination has a n-butane conversion rate of about 38-39%, and an ethylene + propylene yield of about 14-15%. The catalytic performance is significantly better than that of 1% Co-HZSM-5. When the combination is a double bed, the distance between active sites reaches the maximum, and the catalytic activity is also significantly improved. 1% CoO x @S-1 / HZSM-5 has a n-butane conversion rate of 42.89% and an ethylene + propylene yield of 26.2%, while HZSM-5 / 1%CoO x @S-1 n-Butane conversion with 1% CoO x @S-1 / HZSM-5 is close, but the yields of ethylene and propylene are significantly reduced, mainly due to the fact that part of n-butane is converted into 1% CoO x @S-1 After dehydrogenation, the butene produced is directly discharged without further cracking reaction. 1% CoO x @S-1 / HZSM-5 is the best combination, with a butane conversion rate of 42.89% and an ethylene + propylene yield of 26.2%.

[0064] Based on the optimal combination, the active component loading ratio was changed to investigate 1% CoO x The performance of n-butane catalytic cracking reaction when the mass ratio of @S-1 and HZSM-5 catalysts is 0.2 / 0, 0.15 / 0.05, 0.1 / 0.1, 0.05 / 0.15, 0 / 0.2 respectively. The test results are as follows Figure 3-4 ,from Figure 3-4 It can be seen that with the introduction of 1% CoO x With the increase of @S-1 component, the conversion rate of n-butane showed an increasing trend, and the yield of ethylene + propylene showed a trend of first increasing and then decreasing. x @S-1 / HZSM-5 (0.1 / 0.1) is the best mass ratio.

[0065] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane, characterized in that: The following steps are involved: Step S1. providing a dehydrogenation catalyst and a cracking catalyst, coupling the dehydrogenation catalyst and the cracking catalyst to obtain a composite catalyst, and then mixing the composite catalyst and quartz sand and loading them into a reactor for pretreatment; Step S2. providing a mixed feed gas flow of n-butane and N2, and contacting the mixed feed gas flow with a composite catalyst in a reactor under reaction conditions to carry out a catalytic cracking reaction.

2. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The dehydrogenation catalyst in step S1 is selected from CoO x @S-1, one of Pt / Al2O3, ZrO2, Ga2O3 / ZrO2, the cracking performance catalyst is a molecular sieve catalyst, and the molecular sieve catalyst is selected from one of ZSM-5 and SAPO-34.

3. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically includes the following steps: mixing the dehydrogenation catalyst and the cracking catalyst powder, extruding and molding, and sieving to 40-60 mesh to obtain a composite catalyst.

4. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically includes the following steps: extruding the dehydrogenation catalyst and the cracking catalyst respectively, sieving them to 40-60 mesh, and mixing them to obtain a composite catalyst.

5. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically includes the following steps: extruding the dehydrogenation catalyst and the cracking catalyst respectively, sieving them to 40-60 mesh, and then filling them in a double-bed manner, filling the dehydrogenation catalyst in the upper layer of the double bed, and filling the cracking catalyst in the lower layer of the double bed to obtain a composite catalyst.

6. The method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The coupling of the dehydrogenation catalyst and the cracking catalyst in step S1 specifically includes the following steps: the dehydrogenation catalyst and the cracking catalyst are extruded and formed respectively, sieved to 40-60 mesh, and then filled in a double-bed manner, the cracking catalyst is filled in the upper layer of the double bed, and the dehydrogenation catalyst is filled in the lower layer of the double bed to obtain a composite catalyst.

7. The processing method for adjusting the yield of ethylene and propylene in the process of catalytic cracking of n-butane according to claim 1, characterized in that: The mass ratio of the dehydrogenation catalyst to the cracking catalyst in the composite catalyst of step S1 is 1-3:

1.

8. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The pretreatment in step S1 is specifically as follows: 0.1-0.2 g of the composite catalyst is uniformly mixed with 1-2 g of quartz sand and then loaded into the constant temperature zone in the reactor, then heated to 550°C-600°C under a 30-60 ml / min N2 atmosphere, keeping the temperature constant, oxidizing for 30 min under a 30-60 ml / min air atmosphere, then purging for 5-10 min under a 30-60 ml / min N2 atmosphere, and then reducing for 30 min under a 30-60 ml / min H2 and Ar mixed gas atmosphere.

9. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: C4H in step S2 10 The volume ratio of N2 is 1-4:6-9, and the reaction conditions include: the flow rate of the mixed feed gas flow is 20-50 mL / min, the reaction time is 3.5-5 h, and the reaction temperature is 550° C.-600° C.

10. The processing method for adjusting the yield of ethylene and propylene in the catalytic cracking process of n-butane according to claim 1, characterized in that: The composite catalyst is used as a catalyst for the catalytic cracking reaction of n-butane.